Ответ:
Пошаговое объяснение:
91. (2*10³)*(3*10⁻⁵)= 6*10⁻² В
92. (3*10⁻⁴)*(2*10⁸)= 6*10⁴ Б
№91
(2 * 10³) * (3 * 10-⁵) = (2 * 3) * (10³ * 10-⁵) =
6 * 10-²
Ответ: В)
№92
(3 * 10-⁴) * (2 * 10⁸) = (3 * 2) * (10-⁴ * 10⁸) =
6 * 10⁴
Ответ: Б)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
Пошаговое объяснение:
91. (2*10³)*(3*10⁻⁵)= 6*10⁻² В
92. (3*10⁻⁴)*(2*10⁸)= 6*10⁴ Б
Пошаговое объяснение:
№91
(2 * 10³) * (3 * 10-⁵) = (2 * 3) * (10³ * 10-⁵) =
6 * 10-²
Ответ: В)
№92
(3 * 10-⁴) * (2 * 10⁸) = (3 * 2) * (10-⁴ * 10⁸) =
6 * 10⁴
Ответ: Б)